Mass and parish in late medieval England: the use of York - Barnwell, P. S.; Cross, Claire; Rycraft, Ann; Barnwell, P. S. (Spire Books, 2005)
The Mass in its urban setting / Claire Cross and P.S. Barnwell -- The ornaments of the altar and the ministers in Late-Medieval England / Allan B. Barton -- Choral music in York, 1400-1540 / Lisa Colton -- 'Four hundred masses on the four Fridays next after my decease'. The care of souls in fifteenth-century All Saints, North Street, York / P.S. Barnwell -- A York priest and his parish : Thomas Worrall at St. Michael, Spurriergate, York, in the early sixteenth-century / Claire Cross -- Endings and beginnings / Claire Cross -- An introduction to the Requiem Mass in the use of York / P.S. Barnwell, Allan B. Barton and Ann Rycraft -- A note on the reconstructed Requiem Mass held at All Saints', North Street, York, on 20 April 2002 / John Hawes with Lisa Colton -- The Requiem Mass : text and translation / compilers/translators P.S. Barnwell, Allan B. Barton and Ann Rycraft